(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This article attempts to reveal the main reasons for the role of attitudes towards healthy lifestyles among high school students and university graduate students. To carry out scientific work, the author used the methods of questionnaire survey, analytical, logical and statistical. The primary material was obtained using the method of questionnaire survey, in which 30 high school students and 36 students of the Medical University were involved. To substantiate the conclusions in the descriptive statistics of the study results, relative percentages were used. The problem in question is still little studied, therefore, requires more thorough research.